The philosophy of Robert Boyle - Anstey, Peter R., 1962- (Routledge studies in seventeenth-century philosophy, 2000)
This book presents the first integrated treatment of the philosophy of Robert Boyle, one of the leading English natural philosophers of the Scientific Revolution.